Burden and factors associated with depression among elderly in rural areas of Tirupati: A cross-sectional study - Navya Keerthana Punabaka; Visweswara Rao Guthi; Nagaraj Kondagunta; K. V. Chakradhar; Suleman Shareef Mahammad (MRIMS Journal of Health Sciences)
Background: The most common mental health problem affecting the elderly population is depression, which is underdiagnosed and undertreated. Objectives: The objectives of the study were to estimate the prevalence of depression among the elderly and to determine the association of the level of depression with sociodemographic factors in rural areas of Tirupati. Materials and Methods: The present study was a community-based cross-sectional study conducted among the elderly (60 years and above) in the rural field practice area of SVIMS-Sri Padmavathi Medical College for Women, Tirupati. A total of 310 elderly individuals aged 60 years and above were included and interviewed from 6 months from December 2021 to May 2022. The level of depression was assessed by the Geriatric Depression Scale (GDS). IBM SPSS version 26 for Windows was used to analyze the data. Results: A total of 310 older adults were assessed for mental illness using the GDS 30 questionnaire. Among them, 89 (28.5%) were found to be mildly depressed, 20 (6.4%) were severely depressed and 201 (64.4%) were normal. 7.3% of older adults of 60–69 years had severe depression, followed by 70–79 years (4.2%). 10.3% of elderly males and 6.7% of elderly females had severe depression, respectively. Among Hindus, 26% and 4.9% of the elderly had mild depression and severe depression, respectively, and among Muslims, 50% and 16.7% had mild depression and severe depression, respectively. Conclusions: In this study, more than one-third of the rural elderly people were found to have depression. Nuclear families, religion, caste, occupation, lower socioeconomic status, and overweight and obesity were significant factors contributing to the severity of depression among rural elderly.